Client and Provider Experiences in Uganda Suggest Demand for and Highlight the Importance of Addressing HIV Stigma and Gender Norms Within Safer Conception Care - Young, Cynthia R.; Gill, Elizabeth; Bwana, Mwebesa; Muyindike, Winnie; Hock, Rebecca S.; Pratt, Madeline C.; Owembabazi, Moran; Tukwasibwe, · Deogratius; Najjuma, Alice; Kalyebara, Paul; Natukunda, Silvia; Kaida, Angela; et al. (AIDS and Behavior, 2022)
Safer conception counseling supports HIV-serodifferent couples to meet reproductive goals while minimizing HIV transmission risk, but has not been integrated into routine HIV care. We piloted a novel safer conception program in an established public-sector HIV clinic in Uganda to inform future implementation. In-depth interviews and counseling observations explored experiences of program clients and healthcare providers to assess program acceptability, appropriateness, and feasibility. Fifteen index clients (8 women, 7 men), 10 pregnancy partners, and 10 providers completed interviews; 15 participants were living with HIV. Ten observations were conducted. We identified four emergent themes: (1) High demand for safer conception services integrated within routine HIV care, (2) Evolving messages of antiretroviral treatment as prevention contribute to confusion about HIV prevention options, (3) Gender and sexual relationship power inequities shape safer conception care, and (4) HIV-related stigma impacts safer conception care uptake. These findings confirm the need for safer conception care and suggest important implementation considerations.
Keywords: HIV prevention; Safer conception; Sexual and reproductive health; HIV-serodifferent couples; Uganda